The busiest man in England : Grant Allen and the writing trade, 1875-1900 - Morton, Peter, 1946 April 10- (Palgrave Macmillan, 2005)
This book is the first critical biography of Grant Allen (1848-1899) in a century, based on all the surviving primary sources. Despite his lifelong ill health and relatively short life, Allen was a writer of extraordinary productivity and range. About half of his work reflects interests which ran from Darwinian biology to cultural travel guides. His prosperity, however, was underpinned by fiction; he wrote more than thirty novels, including The Woman Who Did, which has attracted much recent attention from feminist critics and historians. "The Busiest Man in England" uses Allen's career to examine the role and status of the freelance author/journalist in the late Victorian period, and analyzes what it took to succeed in this notoriously tough profession